PERLAKUAN AKUNTANSI TANGGUNG JAWAB SOSIAL PERUSAHAAN UNTUK PENGEMBANGAN MASYARAKAT SEKITAR PT SEMEN TONASA - Badollahi, Ismail (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This study aims to analyze the application and treatment of Corporate Social Responsibility (CSR) accounting in an effort to develop communities around companies in PT Semen Tonasa. Research data obtained from primary data and secondary data. Primary data in the form of direct interviews with the company and the community. While secondary data in the form of data obtained from the company's internal data. The method used is descriptive qualitative method. The results showed that the CSR comdev program implemented by PT Semen Tonasa has greatly helped the surrounding community and the community has felt the benefits and has been running effectively, but needs to be followed up on several programs that are still running without extra supervision from the company . The CSR accounting report originates from the current year's profit of 4% in accordance with the RUPS.